Inhibiting 'progressive realisation'? The effect of privatisation on the right to water in Senegal and South Africa - Oloka-Onyango, J. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.